Reliability Of Transvaginal Ultrasound Measured Endometrial Thickness In Diagnosis Of Endometrial Cancer In Postmenopausal Women - Ayesha Bibi; Noreen Majeed; Irum Mushtaq; Shabana Kalsoom; Ruqya Azhar; Mehreen Mehdi (Journal of Rawalpindi Medical College)
Abstract